Inhibitory and Stimulatory Regulation of Rac and Cell Motility by the G(12/13)-Rho and G(i) Pathways Integrated Downstream of a Single G Protein-Coupled Sphingosine-1-Phosphate Receptor Isoform - Sugimoto, Naotoshi (American Society for Microbiology, 2003)
The G protein-coupled receptors S1P(2)/Edg5 and S1P(3)/Edg3 both mediate sphingosine-1-phosphate (S1P) stimulation of Rho, yet S1P(2) but not S1P(3) mediates downregulation of Rac activation, membrane ruffling, and cell migration in response to chemoattractants. Specific inhibition of endogenous Gα(12) and Gα(13), but not of Gα(q), by expression of respective C-terminal peptides abolished S1P(2)-mediated inhibition of Rac, membrane ruffling, and migration, as well as stimulation of Rho and stress fiber formation. Fusion receptors comprising S1P(2) and either Gα(12) or Gα(13), but not Gα(q), mediated S1P stimulation of Rho and also inhibition of Rac and migration. Overexpression of Gα(i), by contrast, specifically antagonized S1P(2)-mediated inhibition of Rac and migration. The S1P(2) actions were mimicked by expression of V(14)Rho and were abolished by C3 toxin and N(19)Rho, but not Rho kinase inhibitors. In contrast to S1P(2), S1P(3) mediated S1P-directed, pertussis toxin-sensitive chemotaxis and Rac activation despite concurrent stimulation of Rho via G(12/13.) Upon inactivation of G(i) by pertussis toxin, S1P(3) mediated inhibition of Rac and migration just like S1P(2). These results indicate that integration of counteracting signals from the G(i)- and the G(12/13)-Rho pathways directs either positive or negative regulation of Rac, and thus cell migration, upon activation of a single S1P receptor isoform.